Daniel Alexander Payne : the venerable preceptor of the African Methodist Episcopal Church - Strobert, Nelson T. (Lanham, MD : University Press of America, 2012)
This detailed biography gives a portrait of the life of Daniel Alexander Payne, a free person of color in nineteenth century Charleston, South Carolina. This work highlights his life as educator, pastor, abolitionist, poet, historiographer, hymn writer, ecumenist, and bishop of the African Methodist Episcopal Church.
The formative years : 1811-1837 -- The transition years : 1837-1856 -- The Wilberforce experience : 1856-1876 -- The waning years : 1877-1893 -- Daniel Alexander Payne : recuperating his legacy.
Includes bibliographical references and index.
Master record variable field(s) change: 600, 610, 650
Keywords: Payne, Daniel Alexander, -- 1811-1893.; African Methodist Episcopal Church -- Clergy -- Biography; Wilberforce University -- Presidents -- Biography; African American college presidents -- Biography; African American scholars -- Biography; African Americans -- Intellectual life -- 19th century; African Americans -- Biography; African American clergy -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Clergy; Clergy; Educators; United States; Electronic books; Biography